The nuclear architecture of NGC 4151: on the path toward a universal outflow mechanism in light of NGC 1068. Issue 2 (4th June 2020) - May, D; Steiner, J E; Menezes, R B; Williams, D R A; Wang, J
ABSTRACT: We report near-infrared integral field spectroscopic observations of the active galactic nucleus NGC 4151 with archive data from the NIFS-Gemini North Telescope. We have selected best-seeing observations (≲0.3 arcsec) that, allied to our methodology of image processing techniques, show structures with spatial resolution comparable to those of the HST . The intricate outflow of NGC 4151 is revisited in light of the results found for NGC 1068, in a previous work, and a very similar dynamic is found: the low-velocity [Fe ii ] emission depicts the glowing walls of an hourglass structure, while the high-velocity gas fills its volume. From this finding, we show that the misalignment between the jet and the NLR is not a projection effect, as previously thought. A molecular outflow is detected for the first time in this galaxy and, just like in NGC 1068, the transition between the molecular and the ionized gas phases comes from the fragmentation of molecular cavity walls into bullets of ionized gas exposed to the central source. Furthermore, it is suggestive that the same geometrical dichotomy between the cones seen in NGC 1068 is found here, with one side, where the cavity is disrupted by the AGN, being more extended than the other. Finally, a new spatial correlation between the high-velocity [Fe ii ] and the soft X-ray emission of [Ne ix ] is found, which is unexpected given the difference between their ionization potentials.